Granite high-efficiency water-permeable composite brick and preparation method thereof
By using ceramic particles, fine powder, white cement, fine natural granite sand, boron-modified cashew phenol and epoxy nano-silicon dioxide in permeable bricks, the insufficient self-cleaning, compression and wear resistance of existing permeable bricks is solved. The problem of this achieves good performance of granite efficient permeable composite bricks.
Patent Information
- Application Number
- CN202411259455.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing permeable bricks have shortcomings in self-cleaning effect, compressive strength and wear resistance, especially the cement-based permeable bricks have a large permeability coefficient, low compressive strength and poor wear resistance.
The composite bricks including ceramic particles, ceramic fine powder, white cement, natural granite fine sand, boron-modified cashew phenol, epoxy nanosilica and cellulose sulfonate water reducer are prepared through specific stirring and molding processes. Permeable composite bricks form products with good self-cleaning, compression resistance and high water permeability characteristics.
It achieves good self-cleaning effect of granite efficient permeable composite bricks, improves compressive strength, and avoids whitening and degradation of water permeability, while maintaining high water permeability.
Smart Images

Figure BDA0005035083780000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite bricks, in particular to a granite high-efficiency water-permeable composite brick and a preparation method thereof. Background Art
[0002] The current permeable bricks basically belong to the coarse aggregate concrete series with stone as aggregate and cement as cementing material. This cement-based permeable brick has the disadvantages of large permeability coefficient, low compressive strength and poor wear resistance. Therefore, how to avoid this phenomenon is the key to solving the problem. For example, patent CN107226662B discloses a large amount of blast furnace heavy slag composite sand-based permeable brick and its efficient preparation method. It makes use of a large amount of industrial waste blast furnace heavy slag, and adopts modified epoxy resin glue and composite cementing system to prepare heavy slag composite sand-based permeable bricks. It has high interlayer bonding strength, short hardening time and wear resistance, but its self-cleaning effect has not been improved. Summary of the invention
[0003] 1. Technical issues to be resolved
[0004] In view of the deficiencies in the prior art, the present invention provides a granite high-efficiency water-permeable composite brick and a preparation method thereof, which has good self-cleaning and pressure-resistant effects.
[0005] (II) Technical solution
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a granite high-efficiency water-permeable composite brick, comprising a base layer and a surface layer, wherein the base layer comprises 120-160 parts by weight of ceramic particles, 110-150 parts by weight of ceramic fine powder, 200-260 parts by weight of white cement, and 80-130 parts by weight of water; the surface layer comprises 550-700 parts by weight of natural granite fine sand, 8-14 parts by weight of boron-modified cardanol, 4-7 parts by weight of epoxy nano-silica, and 0.8-1.3 parts by weight of cellulose sulfonate water reducer.
[0007] Preferably, the preparation method of the boron-modified cardanol is:
[0008] (1) Adding cardanol and 2,2-bis(bromomethyl)-1,3-propylene glycol to an acetone solvent, stirring to dissolve, then adding a sodium hydroxide aqueous solution with a molar concentration of 4-6 mol / L, reacting at 65-80° C. for 4-7 hours, and then dropping dilute hydrochloric acid to neutralize, concentrating to remove the solvent, filtering, washing and drying to obtain an intermediate 1;
[0009] (2) adding perfluorooctanoyl chloride and intermediate 1 to tetrahydrofuran solvent, and then adding triethylamine catalyst thereto, reacting at 50-80° C. for 5-9 hours, and after the reaction is completed, removing the solvent by distillation under reduced pressure, washing, and recrystallizing to obtain intermediate 2;
[0010] (3) Add boric acid to toluene solvent, stir and disperse, then add intermediate 2, raise the temperature to 80-110° C. and react for 7-10 hours. After the reaction is completed, perform vacuum distillation to obtain boron-modified cardanol.
[0011] Preferably, the mass ratio of cardanol to 2,2-bis(bromomethyl)-1,3-propylene glycol in (1) is 1.2-1.8:1.
[0012] Preferably, the mass ratio of perfluorooctanoyl chloride, intermediate 1 and triethylamine catalyst in (2) is 1:1.1-1.4:0.01-0.03.
[0013] Preferably, the mass ratio of boric acid to intermediate 2 in (3) is 1:1.4-1.7.
[0014] Preferably, the method for preparing the granite high-efficiency water-permeable composite brick comprises the following steps:
[0015] S1. Add ceramic particles, ceramic fine powder, white cement and water into a stirrer, stir for 10-20s, and discharge to obtain a base layer;
[0016] S2. Add natural granite fine sand, boron-modified cardanol, epoxy nano-silica, and cellulose sulfonate water reducer into a blender, stir for 20-30 seconds, and evenly spread on the base layer for extrusion molding.
[0017] (III) Beneficial technical effects
[0018] The invention provides a base layer by adding ceramic particles, ceramic fine powder, white cement and water into a stirrer, stirring and discharging the mixture; and adding natural granite fine sand, boron-modified cardanol, epoxy nano-silica and cellulose sulfonate water reducing agent into the stirrer, stirring and evenly spreading the mixture on the base layer for extrusion molding.
[0019] The cardanol contained in the granite high-efficiency water-permeable composite brick has a good self-cleaning effect. The fluorine element contained therein is introduced into the composite brick to form a smooth fluorocarbon layer on the surface of the composite brick that is not easy to adhere to objects. Therefore, it has a good self-cleaning effect. The substitution degree of the fluorine element and the cardanol is increased through boric acid modification, further improving its self-cleaning effect. The composite brick of the present invention also has the characteristics of good pressure resistance, no whitening, and high water permeability. DETAILED DESCRIPTION
[0020] Example 1
[0021] The granite high-efficiency water-permeable composite brick comprises a base layer and a surface layer, wherein the base layer comprises 120 parts by weight of ceramic particles, 110 parts by weight of ceramic fine powder, 200 parts by weight of white cement, and 80 parts by weight of water; and the surface layer comprises 550 parts by weight of natural granite fine sand, 8 parts by weight of boron-modified cardanol, 4 parts by weight of epoxy nano-silica, and 0.8 parts by weight of cellulose sulfonate water reducer.
[0022] The preparation method of the boron-modified cardanol is:
[0023] (1) adding cardanol and 2,2-bis(bromomethyl)-1,3-propylene glycol to an acetone solvent, wherein the mass ratio of cardanol to 2,2-bis(bromomethyl)-1,3-propylene glycol is 1.2:1, stirring to dissolve, then continuously adding a 4 mol / L sodium hydroxide aqueous solution thereto, reacting at 65° C. for 4 h, and then dropping dilute hydrochloric acid to neutralize the reaction, concentrating to remove the solvent, filtering, washing and drying to obtain an intermediate 1;
[0024] (2) adding perfluorooctanoyl chloride and intermediate 1 to tetrahydrofuran solvent, and then continuing to add triethylamine catalyst thereto, wherein the mass ratio of perfluorooctanoyl chloride, intermediate 1, and triethylamine catalyst is 1:1.1:0.01, reacting at 50° C. for 5 h, and after the reaction, removing the solvent by distillation under reduced pressure, washing, and recrystallizing to obtain intermediate 2;
[0025] (3) Boric acid is added to toluene solvent, stirred and dispersed, and then intermediate 2 is added thereto, wherein the mass ratio of boric acid to intermediate 2 is 1:1.4, the temperature is raised to 80° C. and the reaction is carried out for 7 hours. After the reaction is completed, the reaction is carried out under reduced pressure distillation to obtain boron-modified cardanol.
[0026] The preparation method of the granite high-efficiency water-permeable composite brick comprises the following steps:
[0027] S1. Add ceramic particles, ceramic fine powder, white cement and water into a stirrer, stir for 10 seconds, and discharge to obtain a base layer;
[0028] S2. Add natural granite fine sand, boron-modified cardanol, epoxy nano-silica, and cellulose sulfonate water reducer into a blender, stir for 20 seconds, and evenly spread on the base layer for extrusion molding.
[0029] Example 2
[0030] The granite high-efficiency water-permeable composite brick comprises a base layer and a surface layer, wherein the base layer comprises 160 parts by weight of ceramic particles, 150 parts by weight of ceramic fine powder, 260 parts by weight of white cement, and 130 parts by weight of water; and the surface layer comprises 700 parts by weight of natural granite fine sand, 14 parts by weight of boron-modified cardanol, 7 parts by weight of epoxy nano-silica, and 1.3 parts by weight of cellulose sulfonate water reducer.
[0031] The preparation method of the boron-modified cardanol is:
[0032] (1) adding cardanol and 2,2-bis(bromomethyl)-1,3-propylene glycol to an acetone solvent, wherein the mass ratio of cardanol to 2,2-bis(bromomethyl)-1,3-propylene glycol is 1.8:1, stirring to dissolve, then continuously adding a 6 mol / L sodium hydroxide aqueous solution thereto, reacting at 80° C. for 7 h, and then dropping dilute hydrochloric acid to neutralize the reaction, concentrating to remove the solvent, filtering, washing and drying to obtain an intermediate 1;
[0033] (2) adding perfluorooctanoyl chloride and intermediate 1 to tetrahydrofuran solvent, and then continuously adding triethylamine catalyst thereto, wherein the mass ratio of perfluorooctanoyl chloride, intermediate 1, and triethylamine catalyst is 1:1.4:0.03, reacting at 80° C. for 9 h, and after the reaction, removing the solvent by distillation under reduced pressure, washing, and recrystallizing to obtain intermediate 2;
[0034] (3) Boric acid is added to toluene solvent, stirred and dispersed, and then intermediate 2 is added thereto, wherein the mass ratio of boric acid to intermediate 2 is 1:1.7, and the temperature is raised to 110° C. to react for 10 hours. After the reaction is completed, vacuum distillation is performed to obtain boron-modified cardanol.
[0035] The preparation method of the granite high-efficiency water-permeable composite brick comprises the following steps:
[0036] S1. Add ceramic particles, ceramic fine powder, white cement and water into a stirrer, stir for 20 seconds, and discharge to obtain a base layer;
[0037] S2. Add natural granite fine sand, boron-modified cardanol, epoxy nano-silica, and cellulose sulfonate water reducer into a blender, stir for 30 seconds, and evenly spread on the base layer for extrusion molding.
[0038] Example 3
[0039] The granite high-efficiency water-permeable composite brick comprises a base layer and a surface layer, wherein the base layer comprises 140 parts by weight of ceramic particles, 130 parts by weight of ceramic fine powder, 230 parts by weight of white cement, and 105 parts by weight of water; and the surface layer comprises 625 parts by weight of natural granite fine sand, 11 parts by weight of boron-modified cardanol, 5.5 parts by weight of epoxy nano-silica, and 1.05 parts by weight of cellulose sulfonate water reducer.
[0040] The preparation method of the boron-modified cardanol is:
[0041] (1) adding cardanol and 2,2-bis(bromomethyl)-1,3-propylene glycol to an acetone solvent, wherein the mass ratio of cardanol to 2,2-bis(bromomethyl)-1,3-propylene glycol is 1.5:1, stirring to dissolve, then continuously adding a 5 mol / L sodium hydroxide aqueous solution thereto, reacting at 72° C. for 5.5 h, and then dropping dilute hydrochloric acid to neutralize the reaction, concentrating to remove the solvent, filtering, washing and drying to obtain an intermediate 1;
[0042] (2) adding perfluorooctanoyl chloride and intermediate 1 to tetrahydrofuran solvent, and then continuing to add triethylamine catalyst thereto, wherein the mass ratio of perfluorooctanoyl chloride, intermediate 1, and triethylamine catalyst is 1:1.1.25:0.02, reacting at 65° C. for 7 hours, and after the reaction is completed, removing the solvent by distillation under reduced pressure, washing, and recrystallizing to obtain intermediate 2;
[0043] (3) Boric acid is added to toluene solvent, stirred and dispersed, and then intermediate 2 is added thereto, wherein the mass ratio of boric acid to intermediate 2 is 1:1.55, and the temperature is raised to 95° C. to react for 8.5 hours. After the reaction is completed, vacuum distillation is performed to obtain boron-modified cardanol.
[0044] The preparation method of the granite high-efficiency water-permeable composite brick comprises the following steps:
[0045] S1. Add ceramic particles, ceramic fine powder, white cement and water into a stirrer, stir for 15 seconds, and discharge to obtain a base layer;
[0046] S2. Add natural granite fine sand, boron-modified cardanol, epoxy nano-silica, and cellulose sulfonate water reducer into a blender, stir for 25 seconds, and evenly spread on the base layer for extrusion molding.
[0047] Example 4
[0048] The granite high-efficiency water-permeable composite brick comprises a base layer and a surface layer, wherein the base layer comprises 120 parts by weight of ceramic particles, 110 parts by weight of ceramic fine powder, 200 parts by weight of white cement, and 80 parts by weight of water; and the surface layer comprises 550 parts by weight of natural granite fine sand, 8 parts by weight of boron-modified cardanol, 4 parts by weight of epoxy nano-silica, and 0.8 parts by weight of cellulose sulfonate water reducer.
[0049] The preparation method of the boron-modified cardanol is:
[0050] (1) adding cardanol and 2,2-bis(bromomethyl)-1,3-propylene glycol to an acetone solvent, wherein the mass ratio of cardanol to 2,2-bis(bromomethyl)-1,3-propylene glycol is 1.8:1, stirring to dissolve, then continuously adding a 6 mol / L sodium hydroxide aqueous solution thereto, reacting at 80° C. for 7 h, and then dropping dilute hydrochloric acid to neutralize the reaction, concentrating to remove the solvent, filtering, washing and drying to obtain an intermediate 1;
[0051] (2) adding perfluorooctanoyl chloride and intermediate 1 to tetrahydrofuran solvent, and then continuously adding triethylamine catalyst thereto, wherein the mass ratio of perfluorooctanoyl chloride, intermediate 1, and triethylamine catalyst is 1:1.4:0.03, reacting at 80° C. for 9 h, and after the reaction, removing the solvent by distillation under reduced pressure, washing, and recrystallizing to obtain intermediate 2;
[0052] (3) Boric acid is added to toluene solvent, stirred and dispersed, and then intermediate 2 is added thereto, wherein the mass ratio of boric acid to intermediate 2 is 1:1.7, and the temperature is raised to 110° C. to react for 10 hours. After the reaction is completed, vacuum distillation is performed to obtain boron-modified cardanol.
[0053] The preparation method of the granite high-efficiency water-permeable composite brick comprises the following steps:
[0054] S1. Add ceramic particles, ceramic fine powder, white cement and water into a stirrer, stir for 15 seconds, and discharge to obtain a base layer;
[0055] S2. Add natural granite fine sand, boron-modified cardanol, epoxy nano-silica, and cellulose sulfonate water reducer into a blender, stir for 25 seconds, and evenly spread on the base layer for extrusion molding.
[0056] Example 5
[0057] The granite high-efficiency water-permeable composite brick comprises a base layer and a surface layer, wherein the base layer comprises 160 parts by weight of ceramic particles, 150 parts by weight of ceramic fine powder, 260 parts by weight of white cement, and 130 parts by weight of water; and the surface layer comprises 700 parts by weight of natural granite fine sand, 14 parts by weight of boron-modified cardanol, 7 parts by weight of epoxy nano-silica, and 1.3 parts by weight of cellulose sulfonate water reducer.
[0058] The preparation method of the boron-modified cardanol is:
[0059] (1) adding cardanol and 2,2-bis(bromomethyl)-1,3-propylene glycol to an acetone solvent, wherein the mass ratio of cardanol to 2,2-bis(bromomethyl)-1,3-propylene glycol is 1.5:1, stirring to dissolve, then continuously adding a 5 mol / L sodium hydroxide aqueous solution thereto, reacting at 72° C. for 5.5 h, and then dropping dilute hydrochloric acid to neutralize the reaction, concentrating to remove the solvent, filtering, washing and drying to obtain an intermediate 1;
[0060] (2) adding perfluorooctanoyl chloride and intermediate 1 to tetrahydrofuran solvent, and then continuing to add triethylamine catalyst thereto, wherein the mass ratio of perfluorooctanoyl chloride, intermediate 1, and triethylamine catalyst is 1:1.1.25:0.02, reacting at 65° C. for 7 hours, and after the reaction is completed, removing the solvent by distillation under reduced pressure, washing, and recrystallizing to obtain intermediate 2;
[0061] (3) Boric acid is added to toluene solvent, stirred and dispersed, and then intermediate 2 is added thereto, wherein the mass ratio of boric acid to intermediate 2 is 1:1.55, and the temperature is raised to 95° C. to react for 8.5 hours. After the reaction is completed, vacuum distillation is performed to obtain boron-modified cardanol.
[0062] The preparation method of the granite high-efficiency water-permeable composite brick comprises the following steps:
[0063] S1. Add ceramic particles, ceramic fine powder, white cement and water into a stirrer, stir for 10 seconds, and discharge to obtain a base layer;
[0064] S2. Add natural granite fine sand, boron-modified cardanol, epoxy nano-silica, and cellulose sulfonate water reducer into a blender, stir for 20 seconds, and evenly spread on the base layer for extrusion molding.
[0065] Comparative Example 1
[0066] The granite high-efficiency water-permeable composite brick comprises a base layer and a surface layer, wherein the base layer comprises 160 parts by weight of ceramic particles, 150 parts by weight of ceramic fine powder, 260 parts by weight of white cement, and 130 parts by weight of water; and the surface layer comprises 700 parts by weight of natural granite fine sand, 7 parts by weight of epoxy nano-silica, and 1.3 parts by weight of cellulose sulfonate water reducer.
[0067] The preparation method of the granite high-efficiency water-permeable composite brick comprises the following steps:
[0068] S1. Add ceramic particles, ceramic fine powder, white cement and water into a stirrer, stir for 10 seconds, and discharge to obtain a base layer;
[0069] S2. Add natural granite fine sand, epoxy nano-silica and cellulose sulfonate water reducer into a mixer, stir for 20 seconds, and spread evenly on the base layer for extrusion molding.
[0070] The composite bricks prepared in Examples 1-5 and Comparative Example 1 were taken to measure their water permeability coefficient, single brick weight and compressive strength, and the results of alkali whitening after 2 years of use are shown in Table 1 below.
[0071] Table 1: Composite brick performance test.
[0072]
[0073] As can be seen from Table 1, the composite materials obtained in Examples 1-5 of the present invention have better compression and flexural resistance than those in Comparative Example 1, and will not turn white due to alkali.
[0074] The surface wettability of the composite bricks of Examples 1-5 and Comparative Example 1 was characterized according to JC2000D, and the contact angle test was performed.
[0075] Table 2: Contact angle test.
[0076] project Contact angle Example 1 125.8° Example 2 127.6° Example 3 126.1° Example 4 125.3° Example 5 127.2° Comparative Example 1 105.13°
[0077] It can be seen from Table 2 that compared with Comparative Example 1, the contact angles of Examples 1-5 are larger, resulting in the water droplets being unable to spread and being very easy to slide, indicating that the composite bricks prepared by the present invention have better self-cleaning function.
[0078] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A granite high-efficiency water-permeable composite brick, characterized in that: The method comprises a base layer and a surface layer, wherein the base layer comprises 120-160 parts by weight of ceramic particles, 110-150 parts by weight of ceramic fine powder, 200-260 parts by weight of white cement, and 80-130 parts by weight of water; and the surface layer comprises 550-700 parts by weight of natural granite fine sand, 8-14 parts by weight of boron-modified cardanol, 4-7 parts by weight of epoxy nano-silica, and 0.8-1.3 parts by weight of cellulose sulfonate water reducer.
2. The granite high-efficiency water-permeable composite brick according to claim 1 is characterized in that: The preparation method of the boron-modified cardanol is: (1) Adding cardanol and 2,2-bis(bromomethyl)-1,3-propylene glycol to an acetone solvent, stirring to dissolve, then adding a sodium hydroxide aqueous solution with a molar concentration of 4-6 mol / L, reacting at 65-80° C. for 4-7 hours, and then dropping dilute hydrochloric acid to neutralize, concentrating to remove the solvent, filtering, washing and drying to obtain an intermediate 1; (2) adding perfluorooctanoyl chloride and intermediate 1 to tetrahydrofuran solvent, and then adding triethylamine catalyst thereto, reacting at 50-80° C. for 5-9 hours, and after the reaction is completed, removing the solvent by distillation under reduced pressure, washing, and recrystallizing to obtain intermediate 2; (3) Add boric acid to toluene solvent, stir and disperse, then add intermediate 2, raise the temperature to 80-110° C. and react for 7-10 hours. After the reaction is completed, perform vacuum distillation to obtain boron-modified cardanol.
3. The granite high-efficiency water-permeable composite brick according to claim 2 is characterized in that: The mass ratio of cardanol to 2,2-bis(bromomethyl)-1,3-propylene glycol in (1) is 1.2-1.8:
1.
4. The granite high-efficiency water-permeable composite brick according to claim 2 is characterized in that: The mass ratio of perfluorooctanoyl chloride, intermediate 1 and triethylamine catalyst in (2) is 1:1.1-1.4:0.01-0.
03.
5. The granite high-efficiency water-permeable composite brick according to claim 2 is characterized in that: The mass ratio of boric acid to intermediate 2 in (3) is 1:1.4-1.
7.
6. A method for preparing a granite high-efficiency water-permeable composite brick according to any one of claims 1 to 5, characterized in that: The preparation method of the granite high-efficiency water-permeable composite brick comprises the following steps: S1. Add ceramic particles, ceramic fine powder, white cement and water into a stirrer, stir for 10-20s, and discharge to obtain a base layer; S2. Add natural granite fine sand, boron-modified cardanol, epoxy nano-silica, and cellulose sulfonate water reducer into a blender, stir for 20-30 seconds, and evenly spread on the base layer for extrusion molding.
